Shunt Surgery, Right Heart Catheterization, and Vascular Morphometry in a Rat Model for Flow-induced Pulmonary Arterial Hypertension - van der Feen, Diederik E. (J Vis Exp, 2017)
In this protocol, PAH is induced by combining a 60 mg/kg monocrotalin (MCT) injection with increased pulmonary blood flow through an aorto-caval shunt (MCT+Flow). The shunt is created by inserting an 18-G needle from the abdominal aorta into the adjacent caval vein. Increased pulmonary flow has been demonstrated as an essential trigger for a severe form of PAH with distinct phases of disease progression, characterized by early medial hypertrophy followed by neointimal lesions and the progressive occlusion of the small pulmonary vessels. To measure the right heart and pulmonary hemodynamics in this model, right heart catheterization is performed by inserting a rigid cannula containing a flexible ball-tip catheter via the right jugular vein into the right ventricle. The catheter is then advanced into the main and the more distal pulmonary arteries. The histopathology of the pulmonary vasculature is assessed qualitatively, by scoring the pre- and intra-acinar vessels on the degree of muscularization and the presence of a neointima, and quantitatively, by measuring the wall thickness, the wall-lumen ratios, and the occlusion score.